Analysis of the impacts of agricultural incentives on the performance of agricultural value chains - Kassie, Girma T.; Martin, Will; Tokgoz, Simla (International Food Policy Research Institute, 2022)
Agricultural value chains are enormously important for development and poverty reduction in developing countries. Unfortunately, the wide array of forms of intervention used creates serious difficulties in understanding its impacts on agricultural value chains and on the economy in general. This paper reviews recent work to increase transparency of agricultural support measures and to assess their impacts on key outcomes. To do this, it draws lessons from various studies on agricultural incentives, including the global Ag-Incentives database, studies exploring the link between agricultural incentives and value chain development, and studies exploring the links between agricultural incentives and environmental outcomes. Studies highlighted in the Report will allow future researchers to use the described methodologies and tools and apply them to different countries, different contexts, and different commodities. This research portfolio has created a foundation for future work relevant to the five Impact Areas of One CGIAR; namely, nutrition, health, and food security; poverty reduction, livelihoods, and jobs; gender equality, youth, and inclusion; climate adaptation and mitigation; and environmental health and biodiversity.